Pengaruh Persepsi Budaya Organisasi terhadap Kinerja Karyawan Dimediasi oleh Organizational Citizenship Behavior - Mike A.K. Lovihan (University of Merdeka Malang, 2014)
The research is aimed to determine the influence of organizational culture on employee performance mediated by the organizational citizenship behavior (OCB). The sample of the research is 70 persons who worked as an administrative/ a non educative employees in Manado State University. The data collecting in this study uses three types of scale; those are the organizational culture scale, job performance scale, and organizational citizenship behavior scale. The results of multiple regression analysis shows that OCB is not a mediator between organizational culture and job performance correlation. However, when in together organizational culture and OCB have a correlation with job performance with the relational coefficient (R) 0,420 (p=0,004) and by the effective donation (Adjusted R Square) 17,7 %. Organizational culture perception can become OCB predictor with effective contribution mark 10%, while for the job performance have an effective contribution mark 15,2 %. Furthermore, OCB also can become a predictor of job performance with an effective contribution mark 15%.